Central Administration of Ampelopsin A Isolated from Vitis vinifera Ameliorates Cognitive and Memory Function in a Scopolamine-Induced Dementia Model - Yuni Hong; Yun-Hyeok Choi; Young-Eun Han; Soo-Jin Oh; Ansoo Lee; Bonggi Lee; Rebecca Magnan; Shi Yong Ryu; Chun Whan Choi; Min Soo Kim (MDPI AG, 2021)
Neurodegenerative diseases are characterized by the progressive degeneration of the function of the central nervous system or peripheral nervous system and the decline of cognition and memory abilities. The dysfunctions of the cognitive and memory battery are closely related to inhibitions of neurotrophic factor (BDNF) and brain-derived cAMP response element-binding protein (CREB) to associate with the cholinergic system and long-term potentiation. Vitis vinifera, the common grapevine, is viewed as the important dietary source of stilbenoids, particularly the widely-studied monomeric resveratrol to be used as a natural compound with wide-ranging therapeutic benefits on neurodegenerative diseases. Here we found that ampelopsin A is a major compound in V. vinifera and it has neuroprotective effects on experimental animals. Bath application of ampelopsin A (10 ng/µL) restores the long-term potentiation (LTP) impairment induced by scopolamine (100 μM) in hippocampal CA3-CA1 synapses. Based on these results, we administered the ampelopsin A (10 ng/µL, three times a week) into the third ventricle of the brain in C57BL/6 mice for a month. Chronic administration of ampelopsin A into the brain ameliorated cognitive memory-behaviors in mice given scopolamine (0.8 mg/kg, i.p.). Studies of mice's hippocampi showed that the response of ampelopsin A was responsible for the restoration of the cholinergic deficits and molecular signal cascades via BDNF/CREB pathways. In conclusion, the central administration of ampelopsin A contributes to increasing neurocognitive and neuroprotective effects on intrinsic neuronal excitability and behaviors, partly through elevated BDNF/CREB-related signaling.